Pengaruh Literasi Zakat, Altruisme, dan Citra Lembaga terhadap Minat Muzakki Membayar Zakat di Lazis Nurul Falah Surabaya dengan Religiusitas sebagai Variabel Moderasi - Berlian Febrianti; Ach. Yasin (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
There is a significant gap between zakat's potential and its actualization., this is because of people’s habit paying zakat directly to mustahik. This study aims to determine how the influence of zakat literacy, altruism and institutional image on muzakki's interest in paying zakat at LAZIS Nurul Falah Surabaya with religiosity as moderation. In this research, the method used is quantitative method with moderation analysis using Smart PLS. Accidental sampling technique is used in sampling. The results of this study prove that partially the variables of zakat literacy, altruism, institutional image affect the interest of muzakki to pay zakat. Religiosity has no effect on muzakki's interest in paying zakat. Meanwhile, the results of moderation analysis show that religiosity cannot moderate zakat literacy, institutional image, and altruism on muzakki's interest in paying zakat. Keywords: Zakat Literacy, Altruism, Institusional Image, Religiosity, Interest